(untitled) (International journal of artificial intelligence, 2025)
In this article, Isajon Sulton’s novel "The Eternal Wanderer" is analyzed as a vivid example of postmodernist elements in contemporary Uzbek literature. The aim of the study is to identify the artistic and aesthetic principles employed in the work, explain them theoretically, and evaluate them as a new creative direction in national literature. For this purpose, comparative-analytical, semantic, and hermeneutic methods are applied to consistently analyze the intertextuality, fragmentation, ironic tone, metatextuality, and multilayered interpretation of the novel. During the research, quotations from the work are compared with theoretical perspectives, and the philosophical, spiritual, and social layers of the text are systematically interpreted.